Knowledge, awareness and perception on childhood vaccination among indigenous and ethnic minority parents: a mini review / Sakina Roslan and Izzati Abdul Halim Zaki - Roslan, Sakina; Abdul Halim Zaki, Izzati (Faculty of Pharmacy, 2023)
Immunisation is imperative because it prevents two to three million deaths annually. World Health Organisation (WHO) defines immunisation as the process that makes people immune to infection by administering the vaccine. However, indigenous and ethnic minority peoples report low vaccination coverage. To date, there are no reviews in this area to the best of our knowledge. Therefore, this research aims to conduct a review of knowledge, awareness, and perception of childhood vaccination among indigenous and ethnic minority parents. Six databases were searched for appropriate quantitative and qualitative primary research. Studies were selected if they were peer-reviewed, in English, available in full text, and focused on the knowledge, awareness, and perception of the childhood vaccine among indigenous and ethnic minority parents. This review includes eight qualitative research, four quantitative studies, and one mixed-methods study. Twenty-one research examined a variety of children's vaccinations. We observed that participants had limited knowledge, low awareness, and negative attitudes about childhood immunisation based on our findings. It was clear that the indigenous and ethnic minority parents were not aware of childhood vaccination. Therefore, we recommend that the governments of every nation take the initiative and consider continuing education programs and health campaigns to increase their acceptance of childhood vaccinations.